From a Fratricide to a Family Memory - Riina Haanpää (Journal of Ethnology and Folkloristics)
When a research deals with researcher’s own family history, a significant challenge is presented: “What is the significance of the familiarity the researcher has for their object of research? What is the researcher’s role and how their own memories influence their work?” In this article I explore the possibilities my own family history offers by observing a fratricide that took place in my family, as well as the narrations it has created. My grandfather’s brother Veikko, while drunk, stabbed and killed his brother Väinö in Kauhajoki in 1974. In my family, the event has been handled in various ways, and due to its uncommonness it has also been the theme of many stories which unveil our family’s history and present lives as well as the relationships inside the family. I have chosen three interviewees as an object of closer inspection. With these interviews, I explore Väinö’s death and the attitudes towards it: “How has the killing been interpreted inside the family and what has it meant to the family” I also examine the reactions towards the death in the society and the South-Ostrobothnian culture. Because the examined manslaughter is also inside my family viewed as an unusual death, it is interesting to raise conversation on divergent deaths in general. I will thusly also observe the point of views presented in the interviews and examine them in correlation with the researches done on divergent death.